The G‐Triplex DNA1. Issue 8 (17th January 2013) - Limongelli, Vittorio; De Tito, Stefano; Cerofolini, Linda; Fragai, Marco; Pagano, Bruno; Trotta, Roberta; Cosconati, Sandro; Marinelli, Luciana; Novellino, Ettore; Bertini, Ivano; Randazzo, Antonio; Luchinat, Claudio; et al.
<x xml:space="preserve">Abstract</x> Triplex with a twist: Through metadynamics calculations, the thrombin binding aptamer (TBA) has been shown to adopt a stable G‐triplex structural motif, in addition to the usual G‐quadruplex (see scheme). An 11‐mer oligonucleotide was also shown to form a stable G‐triplex, whose structural and thermodynamic properties have been characterized.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>